2017
DOI: 10.1088/1367-2630/aa6ece
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic subunits within a single molecule–surface hybrid

Abstract: Magnetic molecule-surface hybrids are ideal building blocks for molecular spintronic devices due to their appealing tailorable magnetic properties and nanoscale size. So far, assemblies of interacting molecular-surface hybrids needed for spintronic functionality were generated by depositing aromatic molecules onto transition-metal surfaces, resulting in a random arrangement of hybrid magnets due to the inherent and strong hybridization. Here, we demonstrate the formation of multiple intramolecular subunits wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…An inversion of the spin polarization of the hybrid state in comparison to the d-like surface state is reasonable, since we deduced in section III C that the TPT molecules must be strongly hybridized with the Co islands, and a strong hybridization results in a inversion of the spin polarization in agreement with previous combined STM and DFT studies 27,31,32 and model calculations 20 .…”
Section: Cu(111)supporting
confidence: 89%
See 3 more Smart Citations
“…An inversion of the spin polarization of the hybrid state in comparison to the d-like surface state is reasonable, since we deduced in section III C that the TPT molecules must be strongly hybridized with the Co islands, and a strong hybridization results in a inversion of the spin polarization in agreement with previous combined STM and DFT studies 27,31,32 and model calculations 20 .…”
Section: Cu(111)supporting
confidence: 89%
“…The spin-sensitive measurements revealed that the spin polarization varies among the different aromatic rings of the TPT molecule, although the molecules exhibit a highly symmetric adsorption geometry as revealed by atomically resolved STM images and confirmed by ab initio calculations that yield the highest binding energy for the experimentally ascertained adsorption site. Hence, the varying degree of spin polarization on the different aromatic rings cannot stem from a different hybridization of the aromatic rings with the ferromagnetic substrate as recently observed for TPT on Fe/W(110) 27 . Given that the spatially resolved spin asymmetry maps also showed a modulation of the spin polarization on the uncovered parts of the Co islands, we propose to link the appearance of the intramolecular variations of the spin polarization to a superposition of the spin polarization of the TPT molecule and the spatially modulated spin-polarized sp surface state of the Co(111) surface.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The distance between the metallic surface and the first organic layer (truea˜) may be smaller than a . It depends on the specific molecule and its interaction with the surface and could be determined by experimental techniques or ab initio calculations. Here we will use a density functional theory based distance from energy relaxation calculations .…”
Section: Modelingmentioning
confidence: 99%